Modelagem computacional de estruturas de poços quânticos semicondutores para dispositivos optoeletrônicos e spintrônicos - Bezerra, Anibal Thiago (2014)
In the present thesis, we realize a computational modeling of semiconductor structures based on multiple quantum wells with filter barriers and on quantum wells with semiconductor diluted magnetic layers. We numerically solve the time-dependent Schrödinger s equation within the effective mass approximation, using the Split Operator method. Through the time evolved wave functions we access the dynamics quantities as the light assisted couplings of the states, in which the light is described by the inclusion of an oscillating electric field in the Hamiltonian. Then we determine the probabilities of absorption, oscillator strengths of the intersubband transitions induced by the light. Moreover we analyze the transmission probabilities and, in special, the system s photocurrent. The eigenstates and the eigenfunctions of the stationary states are also obtained within the method by simply making an imaginary time evolution. In the first work, the photocurrent of a multiple quantum well structure with filter barriers modulating the continuum above the wells was analyzed as a function of the applied bias. We find out an interesting dependence of the photocurrent with the applied field, as a differential negative photoconductance controlled by the field. We attribute this negative conductance to the interaction between the localized and extended states in the continuum, expressed by anticrossings between these states and the enhancement of the photocurrent at the crossings by the Landau-Zener-Stückelberg-Majorama like transitions. In the second work, it was evaluated the spin polarized photocurrent arising from quantum well s structures of GaMnAs, under light, electric and magnetic fields of few teslas. The study shows the existence of spectral domains in the THz ranges for which the proposed structure is strongly spin selective. For such photon frequencies, the photocurrent is spin polarized and the application of the external electric field reverts the polarization s signal. This behavior suggests the possibility of conveniently simple switching mechanisms. The physics underlying these results is studied and understood in terms of the spin-dependent coupling strengths emerging from the particular potential profiles of the heterostructures. We present two additional works related to the main ones. In the first additional one, we evaluated the dark current of the multiple quantum well structure with and without filter barriers. For doing this, we add totally the transmission probability through the structure in the Levine s model for the dark current. We observe that dark current is considerably reduced for the structure with the filter barriers when compared to the structure without these barriers. In the second additional work, we calculate the photocurrent in a ZnMnSe structure. We observe the generation of a spin polarized photocurrent controlled by the external electric field, as in the case of the GaMnAs structures.